Effects of nutritional intervention with or without metformin on insulin resistance in adolescents with polycystic ovary syndrome: A preliminary study - Łagowska, Karolina; Kapczuk, Karina (Progress in Nutrition, 2021)
The aim of the study is show whether, and to what extent, nutritional interventions (NI )with or without metformin   that effectively result in weight reduction in obese adolescents with Polycystic Ovary Syndrome (PCOS) can help to alleviate insulin resistance. 35 obese adolescents with PCOS and insulin resistance were recruited to the study and they were randomly assigned to one of two subgroups: sixteen to a group given a nutritional intervention and metformin treatment (NM) and nineteen to a group given only nutritional intervention (N). Body weight, body composition, energy and nutrients intake as well insulin and glucose levels were measured at the beginning of the study and after 8 weeks of the NI. In both groups after 8 weeks of  NI the reduction in body weight and fat mass were observed. Fasting insulin concentrations measured after 8 weeks of NI were found to be significantly lower in the MN group. In group N, the 8 weeks of intervention proved insufficient for the changes in fasting insulin concentrations. Longer term studies are needed to see if this therapy can result in sustained decreases in body weight and improvements in insulin resistance.